ANALISIS BUTIR SOAL UJIAN AKHIR SEMESTER (UAS) BAHASA JERMAN KELAS X SEMESTER 1 SMA NEGERI 3 SIDOARJO - Effrilianti, Luly; Pujosusanto, Ari (LATERNE, 2021)
To find out the extent of the development of students in the learning process that has been carried out, an educator needs a test to measure the ability and understanding of the students in receiving material in the learning process for one semester. It is expected to be able to assess the suitability of the material that has been taught. Therefore, it is necessary to analyze the items which are tested in the Final Semester Examination (UAS) to see the quality of the questions whether they are proper or need correction to improve the quality in making the items. Analyzing the items are required the difficulty level of the items, validity, and reliability because not all questions have a good level of difficulty, validity, and reliability. The research question was how the difficulty level of the items, the validity, and reliability of the German Final Exam questions for the tenth grade in the first semester SMA Negeri 3 Sidoarjo. In this study, the objective was to describe the difficulty level of the items, the validity and reliability of the German Final Exam questions for the tenth grade in the first semester SMA Negeri 3 Sidoarjo. This article test used quantitative research. The source of the data in this article test was the answer sheet of the German Final Semester Examination (UAS) for the tenth grade in the first semester SMA Negeri 3 Sidoarjo with a total of 198 students that consist of all class from X IPA and IBB. The data were 20 questions of the German Final Exam for the tenth grade in the first semester SMA Negeri 3 Sidoarjo by five answer choices. As a result of the difficulty level analysis, the items were categorized into 3, easy questions, medium questions, and difficult questions. The result of the German Final Exam questions for the tenth grade in the first semester SMA Negeri 3 Sidoarjo showed that the calculation of the difficulty level of the items was nineteen easy questions, one medium question, and zero difficult questions. The results of the validity calculation, 19 were valid, while 1 item was invalid. Thus, it could be said that 90% of the questions were valid and 10% of the questions were invalid. Meanwhile, the results of the calculation of the German Final Exam for the tenth grade in the first semester SMA Negeri 3 Sidoarjo had a sufficient reliability coefficient because it only had a value of 0.520.